Metodologia para subsidiar a análise de solicitações de ressarcimento por danos, utilizando-se dispositivos de proteção contra surtos - Silva, Orlando Adolfo da (2010)
The study of refunding requests by damage on consumers appliances has attracted attention in both scientific community and power companies. In view of its relevance in the power distribution utility, the topic has stimulated scientific research aimed at developing reliable tools to assist decisions towards the analysis of the relationship between equipment damage and system disturbances. In this sense, the main works in progress related to the subject point out on the evaluation the use of computational resources. It s noted that there are no sufficient studies concerning the prevention of possible conflicts arising from damage caused by faults in the distribution system have been conducted so far. In this context, this dissertation focuses its efforts on perfecting previous publications developed in this research area. The main issues addressed in this work relate to knowledge of the characteristics of refunding requests made to the power distribution utility, study and computational implementation of mitigation devices, as well as assessing the consistency of the proposed model through a study of real cases.